LMP1 promoter sequence analysis in Epstein Barr virus pediatric infection reveals preferential circulation of B95.8 related variants in Argentina - Gantuz, Magdalena (2013)
The Epstein Barr virus (EBV) is associated with several lymphoid and epithelial malignancies such as Hodgkin and Burkitt lymphoma or nasopharyngeal carcinoma and it is also the etiological agent of infectious mononucleosis (IM). Transcriptional regulation of the viral oncoprotein LMP1, remains yet not fully understood. LMP1 expression can be initiated in an EBNA2 dependent or independent manner from ED-L1 or LT-R1 promoters. It has been proposed that sequence variation at ED-L1 region could be an important factor concerning LMP1 expression. In order to characterize the natural sequence variation of the ED-L1 promoter, and its relationship with neoplasia, 44 pediatric patients, 17 IM and 27 EBV-associated lymphoma cases from Argentina, were studied. Phylogenetic analysis showed 4 main clusters, namely B95.8, Raji, Cao and P3HR1. Most isolates, 80.3%, conformed the B95.8 group. Co-infection with more than one viral variant was detected in 5/17 IM cases, but no co-infections were detected among lymphoma cases. Moreover, co-infected IM cases exhibited differences between the ED-L1 sequences obtained from different anatomical compartments. Mutations confined to transcription factor binding sites such as SP1/SP3, CRE, AP2, C/EBP were found in similar proportions in 23 isolates from both benign and malignant samples, rendering the distribution of these mutations not significant among malignant samples.